PENGARUH KEPUASAN DAN PERSEPSI TERHADAP PELAYANAN KONSUMEN PADA KANTONG PLASTIK BERBAYAR DI ALFAMART KOTA MEDAN ( KAJIAN LITERATUR REVIEW ) - Efry Kurnia; Roza Maya Sari; Novi Aisha (Cangkal : Jurnal Ilmu Sosial Dan Humaniora, 2025)
The paid plastic bag policy in supermarkets is an environmental policy response aimed at reducing the use of single-use plastics, encouraging the adoption of eco-friendly bags, and increasing sustainability awareness among consumers. This article uses a literature review on consumer perceptions and satisfaction levels with paid plastic bag services at Alfamart in Medan. The main objective is to summarize findings from various previous studies on how plastic bag fees affect perceived value, satisfaction, shopping experience, and customer loyalty. Literature findings indicate that plastic bag fees are often perceived as a fair additional cost if the overall utility value of shopping remains high, and encourages the adoption of repeat bags or environmentally friendly alternatives. Factors influencing satisfaction include the clarity of cost information at the cashier, the availability of cost-effective paid bag options, transaction convenience, and perceptions of Alfamart's environmental responsibility in Medan